Gambling and football : epidemiological research on gambling participation and problem gambling among adult football players in Iceland - Tryggvi Þór Einarsson 1990- (2016)
There is not much known about the gambling behaviour of Icelandic football players. Aims of the current study were to examine the prevalence of total gambling participation and problem gambling among Icelandic football players, to examine if Icelandic football players have been involved in behaviour that could possibly be related to game fixing and to examine players attitudes towards banning coaches and players to gamble on games the Icelandic championship. Participants were 725, of which 75% were men and 25% were women. Mean age of participants was 23.2 (sd=4.3). Past year gambling participation was 66%; men (78%) gambled significantly more than women (29%). Gambling participation was 76%- 79% in all men’s divisions but one, in Inkasso-deildin gambling participation was 66%. About 32% of women in 1st division had gambled and about 16% in women’s Pepsi-deild. The most popular gambling activity was sports gambling, and then came the lottery, poker, scratch tickets, and Electronic Gambling Machines. Problem gambling was evaluated with Problem Gambling Severity Index PGSI and 9.6% of participants were problem gamblers. Players who gambled more frequently on football on foreign websites were significantly associated with gambling on their own team. Interestingly, about 23% of participants knew about other players or coaches that had gambled on matches involving their own team, but only 7% of players said they gambled on their own team in a match, and 2% had gambled on in-play events in matches involving their own team. Problem gambling was significantly associated with thinking that KSÍ should not ban players and coaches from gambling on Icelandic matches. This study indicates that match fixing might possibly be a problem in Icelandic football and that players might need education on the possible risk that follows such behaviour.